Perancangan Aplikasi Web Kredit Mikro Menggunakan UML (Unified Modeling Language) Dan Framework PHP Codeigniter - Simon Surya Keban (LPPM STIKOM Tunas Bangsa, 2023)
Community Based Water Supply and Sanitation Program (Pamsimas) is a program that aims to support and increase access of drinking water facilities to local people. One of the Pamsimas programs in increasing the capacitation of KPSPAMS or infrastructure for water supply and sanitation is Micro Credit. In certain areas reporting and storing data are not monitored and effective, where it is difficult to monitor and store complete data reports. The purpose of this research is to design a microcredit web application using the UML (Unified Modeling Language) design tool and the PHP Codeigniter Framework in Jakarta Pamsimas Program. The result of this research is Micro Credit Program web application that can be used by community facilitators and District Coordinators in inputting KPSPAM data that follows the Micro Credit program in the payment process.